Journal of Cold War studies - Harvard Project on Cold War Studies.; Davis Center for Russian and Eurasian Studies. (MIT Press, 1999)
Published by Davis Center for Russian Studies, Harvard University. Sponsored and edited by the Harvard Project on Cold War Studies, Harvard University. Special issues: Vol. 4, No. 3: Italy and the Cold War.Current frequency: 4/year, 2002-